Penerapan Metode Taqriri Dalam Menghafal Al-Qur'an Pada Santri Madrasah Dinniyah - Siti Nur Inayah; Nafiah Nafiah; M. Suyudi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The taqriri method, which is a learning technique based on repetition and confirmation of material, is expected to improve students' understanding and learning outcomes in the context of religious education. This research aims to analyze the implementation of the taqriri method on the learning outcomes of students at Madin Syekh Subaqir Sukorejo Ponorogo. This research used a qualitative approach by conducting direct interviews with 3 teachers and 15 students in grades 3 and 4 of TPQ Sheikh Subakir Sukorejo Ponorogo. The data collection technique used was through direct interviews and also conducting observations at TPQ Sheikh Subakir Sukorejo Ponorogo. The results of the research show that the application of the taqriri method has a positive effect on improving student learning outcomes, which is indicated by significant improvements in grades and understanding of teaching material. These findings suggest that the taqriri method should be widely applied in the learning process to improve the quality of education in these institutions, Applying this method to learning to memorize the Al-Qur'an will be more impressive and easier for students, making it easier for students to memorize the Al-Qur'an.